PENGELOLAAN BEBAN KOGNITIF PADA TUGAS KOMPLEKS BAGI PESERTA DIDIK SEKOLAH DASAR - Didit Darmawan; Anis Shofa; Nur Rahma Febryanti; Arya Putra Ramadhani; Muhammad Ali Fikri (Prodi PGMI STAI Sabili Bandung, 2026)
Cognitive load management during complex tasks represents a fundamental challenge for elementary school students, whose working memory capacity remains limited and metacognitive abilities are still developing. This qualitative literature review explores how young learners experience and manage cognitive load when confronted with complex academic tasks, synthesizing theoretical perspectives from cognitive psychology and instructional design. The investigation reveals that elementary school students employ varied strategies ranging from simple repetition to rudimentary task segmentation, though most strategies remain unstructured and suboptimal without explicit guidance. External factors including instructional design, teacher support, and physical learning environment substantially influence students' success in managing cognitive load. Individual differences in working memory capacity, prior knowledge, and emotional regulation shape diverse experiences among students facing similar tasks. Effective cognitive load management requires minimizing extraneous load through well designed instruction, managing intrinsic load by aligning task difficulty with developmental readiness, and optimizing germane load through activities that promote schema construction. The development of metacognitive awareness plays a crucial role, enabling students to recognize overload conditions and adjust strategies accordingly. Peer collaboration, when properly structured, can distribute cognitive load and enhance learning outcomes. The experiences of cognitive load management during elementary years have long term implications for the formation of academic dispositions and resilience. The study contributes foundational understanding for designing developmentally appropriate learning experiences that respect the cognitive capacities of young learners